Exploring the Solubility and Bioavailability of Sodium Salt and Its Free Acid Solid Dispersions of Dolutegravir - Dani Lakshman Yarlagadda; Akshatha M. Nayak; Bheemisetty Brahmam; Krishnamurthy Bhat (Advances in Pharmacological and Pharmaceutical Sciences)
Amorphous salt solid dispersion (ASSD) of Dolutegravir amorphous salt (DSSD) was generated using quench cooling and compared to its Dolutegravir free acid solid dispersion (DFSD) to improve the solubility and bioavailability. Soluplus (SLP) was used as a polymeric carrier in both solid dispersions. The prepared DSSD and DFSD, physical mixtures, and individual compounds were characterized by employing DSC, XRPD, and FTIR to assess the formation of the single homogenous amorphous phase and the existence of intermolecular interactions. Partial crystallinity was observed for DSSD, unlike DFSD, which is completely amorphous. No intermolecular interactions were observed between the Dolutegravir sodium (DS)/Dolutegravir free acid (DF) and SLP from the FTIR spectra of DSSD and DFSD. Both DSSD and DFSD improved the solubility of Dolutegravir (DTG) to 5.7 and 4.54 folds compared to the pure forms. Similarly, drug release from DSSD and DFSD was 2 and 1.5 folds higher than that in the pure form, owing to the rapid dissolution of the drug from the formulations. The permeability of DSSD and DFSD was estimated using the dialysis membrane, which enhanced the DTG permeability. The improvement in in vitro studies was translated into in vivo pharmacokinetic profiles of DSSD and DFSD, where 4.0 and 5.6 folds, respectively, improved the Cmax of DTG.